Novel Therapeutic Approaches Enhance PGC1-alpha to Reduce Oxidant Stress-Inflammatory Signaling and Improve Functional Recovery in Hibernating Myocardium - Rishav Aggarwal; Koray N. Potel; Edward O. McFalls; Tammy A. Butterick; Rosemary F. Kelly (Antioxidants, 2022)
Ischemic heart disease affects millions of people around the world. Current treatment options, including coronary artery bypass grafting, do not result in full functional recovery, highlighting the need for novel adjunctive therapeutic approaches. Hibernation describes the myocardial response to prolonged ischemia and involves a set of complex cytoprotective metabolic and functional adaptations. PGC1-alpha, a key regulator of mitochondrial energy metabolism and inhibitor of oxidant-stress-inflammatory signaling, is known to be downregulated in hibernating myocardium. PGC1-alpha is a critical component of cellular stress responses and links cellular metabolism with inflammation in the ischemic heart. While beneficial in the acute setting, a chronic state of hibernation can be associated with self-perpetuating oxidant stress-inflammatory signaling which leads to tissue injury. It is likely that incomplete functional recovery following revascularization of chronically ischemic myocardium is due to persistence of metabolic changes as well as prooxidant and proinflammatory signaling. Enhancement of PGC1-alpha signaling has been proposed as a possible way to improve functional recovery in patients with ischemic heart disease. Adjunctive mesenchymal stem cell therapy has been shown to induce PGC1-alpha signaling in hibernating myocardium and could help improve clinical outcomes for patients undergoing bypass surgery.